Traditonal use of medicinal herbs by local community of Wawonii island, Southeast Sulawesi - MULYATI RAHAYU; SITI SUNARTI; DIAH SULISTIARINI; SUHARDJONO PRAWIROATMODJO (Society for Indonesian Biodiversity, 2006)
Twice field works to Wawonii Island was carried out in 2003 and 2004, in order to collect data on utilization of medicinal plants by local people. Two villages of Wawonii, which occupied by Wawonii tribe, were selected as study sites. Based on the study of 73 plants species, which uses by local people as traditional medicine and after having child were recorded. Similar to order inland areas of Indonesia, forest clearances and process of modernization was also occurred in this study area. Consequence the effect of those activities expected will beaffect in lost of local knowledge and destruction of natural resources. For that reason a study on utilizes of medicinal plant by local people is needed.Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKeywords: traditional medicine; Wawonii tribe; Southeast Sulawesi.